Simulation and Comparative Analysis of PID and LQR Controllers for Speed Control of a BLDC Motor Based on State-Space Model - Wahab, Faisal (Emitor: Jurnal Teknik Elektro, 2025)
This study explores the performance of Proportional-Integral-Derivative (PID) and Linear Quadratic Regulator (LQR) controllers in regulating BLDC motor speed. The PID controller is tuned using both MATLAB-based auto-tuning and manual parameter selection, while the LQR controller is designed by adjusting the Q and R matrices through iterative optimization. To evaluate their effectiveness, a mathematical model of the BLDC motor is developed in a state-space representation, enabling simulation of its dynamic response. The open-loop system shows a slow response and significant steady-state error, making it unsuitable for precise speed control. The PID tuner improves response time and accuracy, it introduces overshoot. Manual tuning further refines performance by reducing overshoot and enhancing stability. The LQR controller demonstrates the fastest response, minimal overshoot, and the lowest steady-state error, making it the most effective approach for BLDC motor speed regulation